Paying Out of Pocket for Healthcare in Bangladesh - A Burden on Poor? - Nazmul M HUQ; AbulQuasem AL-AMIN; SushilRanjan HOWLADER; MohammadAlamgir KABIR (Tehran University of Medical Sciences, 2015)
Letter to the Editor